Fluorination of underdoped mercurocuprate superconductors - Peacock, G; Fletcher, A; Slaski, M; Gameson, I; Capponi, J; Edwards, P (1998)
We present the results of a study into the incorporation of fluorine into the mercurocuprate superconductors. In all cases, the effect of fluorination has been to increase the Tc of underdoped superconductors to the maxima reported. This has important ramifications for the role of the interstitial oxygen in the mercurocuprate superconductors. To assist us in our study, we have, additionally, developed a novel synthetic procedure for preparing HgBa2CuO4+δ in a highly underdoped state. Remarkably, this material shows an increase in Tc, upon fluorination, of 60K! © 1998 Plenum Publishing Corporation.